Reply to Del Guacchio et al. The Genus Lophiolepis Is at Least as Well Supported as Afrocarduus, Afrocirsium, and Nuriaea. Comment on “Moreyra et al. African Mountain Thistles: Three New Genera in the Carduus-Cirsium Group. Plants 2023, 12, 3083” - Lucía D. Moreyra; Alfonso Susanna (Plants)
We recently published a paper that presented the first Hyb-Seq phylogeny for subtribe Carduinae, in which we described three new genera endemic to the African Sky-Islands [...]